2021
DOI: 10.1038/s41557-021-00707-0
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 simulations go exascale to predict dramatic spike opening and cryptic pockets across the proteome

Abstract: SARS-CoV-2 has intricate mechanisms for initiating infection, immune evasion/suppression and replication that depend on the structure and dynamics of its constituent proteins. Many protein structures have been solved, but far less is known about their relevant conformational changes. To address this challenge, over a million citizen scientists banded together through the Folding@home distributed computing project to create the first exascale computer and simulate 0.1 seconds of the viral proteome. Our adaptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
245
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 212 publications
(252 citation statements)
references
References 98 publications
(100 reference statements)
7
245
0
Order By: Relevance
“…This strongly indicates that CoV-1 S become relatively much flexible, generating a large conformational ensemble with less potential for binding with hACE2. This result is consistent with the recent observations in an extensive 0.1 second MD simulation which noted a large opening of spike with presence multiple cryptic epitopes [40]. In contrast, when RBD binds with hACE2, CoV2-RBD-hACE2 becomes relatively more rigid than CoV1-RBD-hACE2, which favours proteolytic processing for membrane fusions.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This strongly indicates that CoV-1 S become relatively much flexible, generating a large conformational ensemble with less potential for binding with hACE2. This result is consistent with the recent observations in an extensive 0.1 second MD simulation which noted a large opening of spike with presence multiple cryptic epitopes [40]. In contrast, when RBD binds with hACE2, CoV2-RBD-hACE2 becomes relatively more rigid than CoV1-RBD-hACE2, which favours proteolytic processing for membrane fusions.…”
Section: Resultssupporting
confidence: 92%
“…This is in agreement with rigidity analysis (Figure 8A, Table2), where we have shown that SARS-CoV-2 retains its overall rigidity better than SARS-CoV-1. Furthermore, large-scale computing efforts via Folding@home project have carried out millisecond MD simulation [40], where it was shown the RBD domain in the up state of the SARS-CoV-1 exhibits higher deviation from the respective crystal structure in comparison to the SARS-CoV-2 [40]. Interestingly, one of the RBDs in SARS-CoV-1 that is initially in the down configuration transitions to the open configuration.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, over a million citizen scientists performed an unprecedented 0.1 s of MD simulations through the Folding@home computing project to create the world’s first Exascale computer and simulate protein dynamics of SARS-CoV-2. 82 This, in turn, revealed how the S-protein of SARS-CoV-2 uses conformational masking to evade host immunity and subsequently identified the hidden cryptic pockets that were not captured or were extremely difficult to capture in experiments. A consortium of high-performance computing (HPC) for research on COVID-19 was constituted in early 2020.…”
Section: Applications Of Supercomputer-assisted MD Simulationsmentioning
confidence: 97%
“…We performed detailed statistical analysis of RBD deviations and RBD-W H bonds provide a comparison of the movement of the residues in RBD (ARG319-PHE541), and even RBM (SER438-GLN506) [30,31]. These analyses intend to address the following widely known observations.…”
Section: The Measurements In Rbdsmentioning
confidence: 99%
“…S protein is decorated extensively with glycans that aid in immune evasion by shielding potential antigens [32,33]. S protein uses a conformational masking strategy, wherein it predominantly adopts a closed conformation that retract the RBDs to escape immune surveillance mechanisms, and then the RBD needs to open to intersect with ACE2 [31].…”
Section: The Measurements In Rbdsmentioning
confidence: 99%